PENGARUH LAMA USAHA, TINGKAT PENDIDIKAN, DAN TEKNOLOGI TERHADAP PENDAPATAN UMKM FURNITUR DI MENGANTI - Puput Aprila; Anita Handayani; Abdurrahman Faris Indriya Himawan; Nur Cahyadi (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
This research is motivated by the increasing number of new furniture UMKM during the covid-19 pandemic which causes the income they get to be not optimal, due to competition with existing furniture UMKM. So that the owners of the new UMKM furniture should consider more about the experience, knowledge, and technological developments. This study aims to explain the effect of length of business, level of education, and technology on the income of UMKM furniture in Menganti. This research is research with a quantitative approach. The location of this research is in the Menganti. The variables in this study are the length of business, level of education, and technology. The population in this study are the owners of UMKM furniture in Menganti. The sample in this study were all owners of UMKM furniture in Menganti, totaling 93 owners. Sampling technique with a saturated sample. The data collection technique used is by distributing questionnaires. The data analysis technique used a descriptive statistical technique. The results of the study show that the length of business, education level, and technology have a positive and significant effect on income. The conclusion of this study is the length of business, education level, and technology have a positive and significant effect on the income of the owners of UMKM furniture in Menganti.